2023
DOI: 10.1039/d3cc04709a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in the use of Bobbitt's salt and 4-acetamidoTEMPO

Jean M. Bray,
Shannon M. Stephens,
Shayne M. Weierbach
et al.

Abstract: This feature article provides a comprehensive overview of recent developments and applications of Bobbitt's salt and 4-acetamidoTEMPO in organic synthesis and fields beyond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 178 publications
(425 reference statements)
0
6
0
Order By: Relevance
“…This control experiment reinforced a desaturation mechanism involving the ester n(O)-to-σ*(C−H) activation rather than the allylic π(C�C)-to-σ*(C−H) activation. 36 At present, we cannot rule out a mechanism involving enol formation from substrate 2 followed by desaturation by oxoammonium salt 30 which was also proposed in the literature. 33,34 Although DFT computations (r 2 SCAN-3C/ CPCM (CH 2 Cl 2 )) showed that the enol desaturation is almost barrierless (TS-SB, 2.3 kcal/mol), 9 we were unable to identify an energetically reasonable enolization process.…”
Section: Journal Of Thementioning
confidence: 78%
See 2 more Smart Citations
“…This control experiment reinforced a desaturation mechanism involving the ester n(O)-to-σ*(C−H) activation rather than the allylic π(C�C)-to-σ*(C−H) activation. 36 At present, we cannot rule out a mechanism involving enol formation from substrate 2 followed by desaturation by oxoammonium salt 30 which was also proposed in the literature. 33,34 Although DFT computations (r 2 SCAN-3C/ CPCM (CH 2 Cl 2 )) showed that the enol desaturation is almost barrierless (TS-SB, 2.3 kcal/mol), 9 we were unable to identify an energetically reasonable enolization process.…”
Section: Journal Of Thementioning
confidence: 78%
“…Although allylic alcohols tend to be reactive toward such reagents, , we reasoned that the ester of 2 might prevent alcohol oxidation, as we only recovered starting material 2 after treatment with DDQ. Based on a literature search that identified Bobbitt’s oxoammonium salt 30 as a stoichiometric reagent for both oxidation of alcohols and desaturation of ketones, we found that 30 cleanly converted allylic alcohol 2 to nidulalin A ( 1 ) in 78% yield in refluxing DCE without alcohol oxidation (Figure A). On the other hand, use of AZADO-BF 4 32 resulted in decomposition, and TEMPO-BF 4 31 only resulted in a lower yield of 1 along with unidentified byproducts.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As [1,2]-Wittig products are traditionally expected to be generated via a radical recombination mechanism the effect of adding 20 mol% of 4-NHAc-TEMPO as an additive was probed. Formation of the [1,2]-product was not significantly inhibited, giving 9 in 73% yield and improved 95:5 er, with no 4-NHAc-TEMPO adducts observed 33 . The mass balance consisted of the aldol side product 10 (>95:5 dr, 75:25 er) that was isolated in 5% yield; addition of 1.0 equivalent of 4-NHAc-TEMPO was also tested, affording 9 in a further reduced 59% yield but enhanced 97:3 er.…”
Section: Reaction Developmentmentioning
confidence: 96%
“…26,28 We focused on TEMPO-derived oxoammonium salts, specifically 4acetamido-2,2,6,6-tetramethylpiperidine-1-oxoammonium tetrafluoroborate, commonly known as "Bobbitt's salt", which is known in organic chemistry for its ability to selectively oxidize alcohols to aldehydes and carboxylic acids without the need of metal catalysis. 31,32 Notably, recent work by Xu et al demonstrated the use of Bobbitt's salt for the oxidation of a modified DNA base, 5-hydroxymethyl cytosine, to its corresponding aldehyde and their protocol showed no adverse effects of the integrity of DNA. 33 This oxoammonium saltmediated oxidation process does not rely on stoichiometric secondary or terminal oxidants, which lessens additional risks from potential DNA damage by an extra oxidant or unexpected scale effects from additional reaction turnover steps.…”
mentioning
confidence: 99%